Cross-Country Evidence on the Relationship between Overwork and Skilled Women's Job Choices - Cortes, Patricia; Pan, Jessica (American Economic Review, 2017)
This paper examines the relationship between the prevalence of overwork and skilled women's labor force participation and occupational choice. Using country-level variation, we find a negative relationship between the share of males working 50+ hours a week and the LFP of young married women, with the correlation being much smaller for single women and older married women. Using a panel of occupations across countries, we find that overwork in an occupation is negatively correlated with the share of married women working in that occupation. This finding is robust to controlling for the occupational distribution of groups with fewer household responsibilities.